Ritual memory : the apocryphal Acts and liturgical commemoration in the early medieval West (c. 500-1215) - Rose, Els, 1972- (Mittellateinische Studien und Texte ;, 2009)
Presents an analysis of the liturgical celebration of the apostles in the medieval West and examines the incorporation of the apocrypha in practices of ritual commemoration. This book reveals the role that liturgy played in the transmission of the apocryphal Acts.